2022
DOI: 10.1007/s15010-022-01755-5
|View full text |Cite
|
Sign up to set email alerts
|

One-year evolution of DLCO changes and respiratory symptoms in patients with post COVID-19 respiratory syndrome

Abstract: Purpose During a follow-up program of patients admitted for COVID-19 at our non-ICU Unit, we found that 37% of them had decreased diffusing lung capacity for carbon monoxide (DLCO) 3-6 months after discharge. This prospective observational study aimed to evaluate the evolution of changes in DLCO and respiratory symptoms at the 1-year follow-up visit. Methods Seventeen (mean age 71 years; 8 males) of 19 eligible patients (DLCO < 80% of predicted at the 3-6 months follow-up visit) completed the 1-year follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Among the 193 studies under full-text review, 153 studies were excluded. Eventually, 40 studies were included in this meta-analysis based on the inclusion criteria [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 193 studies under full-text review, 153 studies were excluded. Eventually, 40 studies were included in this meta-analysis based on the inclusion criteria [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of DLCO has been considered the main determinant of dyspnea in PCS [30]. Nevertheless, many recent evidence showed that DLCO tends to normalize or improve after 1 year, despite a non-neglectable number of patients in whom respiratory symptoms persist [12] and dyspnea remains, therefore, still unexplained. Also pulmonary function [31,32] and cardiopulmonary exercise testing [33] do not show clear alterations in COVID-19 survivors experiencing PCS associated dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…New onset dyspnea after COVID-19 has been associated with an increase of peripheral airway resistances [9,10] and/or a reduced diffusion lung capacity (DLCO) [11][12][13]. These phenomena may derive from the impairment of the peripheral lung (inhomogeneity of peripheral ventilation, airway/parenchyma damage, microvascular abnormalities, or a combination of these events) and even though many studies based on CT scan looked for anatomical abnormalities, the functionality of this lung region is still largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…These include the actual boundaries of the PASC symptom constellation, its similarity and peculiarities in relation to other viral diseases, its actual frequency and relevance in the pediatric population. Some of the symptoms and imbalances characteristic of PASC tend to last up to months, but are ultimately going to disappear, although in a minority of patients, anosmia, brain "fog", DPCO, and dyspnea can persist after one year even among young and middle-aged adults after mild acute SARS-CoV-2 infection and impact on general health and working capacity [115][116][117]. Females showed significantly more neurocognitive symptoms than males.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%